Kebiasaan Belajar Mahasiswa Ditinjau Dari Self-Management dan Penyesuaian Diri - Yansen Alberth Reba; Natalia Horota; Musa Hefer Smas; Meggy Merlin Mokay (Universitas Kanjuruhan Malang, 2021)
The objectives of the present study were: 1) to analyze the correlation between self-management and study habit, 2) to analyze the correlation between academic self-adjustment and study habit, 3) to analyze the magnitude of the correlation between self-management, academic self-adjustment and study habit of the college student. This is a quantitative study that applies multiple correlational analysis method. The study population involved Guidance and Counseling students from the Faculty of Teacher Training and Education, Cenderawasih University, Class of 2017, 2018, 2019, 2020 as many as 60 students. The research sampling of the study employed non-probability sampling through total quota sampling method. The utilization of the method allowed all students to be the research sample. Based on the research findings, there was no significant correlation between self-management and study habit of the college student. There was a significant correlation between self-adjustment and study habit of the college student. There was a correlation between self-management with self-adjustment and study habit of the college student. Meanwhile, the simultaneous contribution of self-management with self-adjustment and study habit variables was 35% (0.350) while the other 65% was determined by other variables that affect study habit.